When archaeology meets environmental sciences: the Bruszczewo site revisited - Niebieszczański, Jakub; Gałka, Mariusz; Hildebrandt-Radke, Iwona; Karpińska-Kołaczek, Monika; Kołaczek, Piotr; Lamentowicz, Mariusz; Rzodkiewicz, Monika (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
Settlement archaeology is often supported by geoarchaeology in which human habitation is drawn on the timeframe of landscape changes derived through interdisciplinary research. An example of a geoarchaeological approach to settlement study is the Bruszczewo Lake project conducted in Central-Western Poland. The area of Bruszczewo and the Samica River Valley witnessed human occupation since the Neolithic period and is most widely known for the presence of an Early Bronze Age fortified settlement. Previous research provided initial information about the presence of a lake and marshland in prehistoric and early historical times. A new geoarchaeological project aims to create a detailed environmental and landscape transformation history combined with the extensive knowledge of the archaeology of the area. Using GIS techniques, conventional drilling, and vibra-coring, a new set of data is brought to light and analysed in palaeoenvironmental terms. Constructed geological profiles across the valley revealed the basin’s morphology and provided insight into the subsequent landscape transformation phases, from the Late Glacial ribbon lake lasting until the end of the Bronze Age to the marshlands that thrived until the Early Medieval period. The ongoing analyses of samples derived from drillings provide a perspective for detailed reconstructions of landscape changes.
Keywords: Geoarchaeology; Environmental Archaeology; Bruszczewo; Palaeoecology